2011
DOI: 10.1016/j.jmig.2011.08.044
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Novel Virtual Reality Simulator for Robotic Surgery

Abstract: Objective. With the increase in robotic-assisted laparoscopic surgery there is a concomitant rising demand for training methods. The objective was to establish face and construct validity of a novel virtual reality simulator (dV-Trainer, Mimic Technologies, Seattle, WA) for the use in training of robot-assisted surgery. Methods. A comparative cohort study was performed. Participants (n = 42) were divided into three groups according to their robotic experience. To determine construct validity, participants perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…With regard to content validity, it widely refers to experts’ judgement towards the learning content and tasks of a simulator [ 14 , 17 , 27 29 ]. Nevertheless, many published studies rely on subjects with different levels of experience in evaluating content validity of a simulator [ 12 , 13 , 22 , 30 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to content validity, it widely refers to experts’ judgement towards the learning content and tasks of a simulator [ 14 , 17 , 27 29 ]. Nevertheless, many published studies rely on subjects with different levels of experience in evaluating content validity of a simulator [ 12 , 13 , 22 , 30 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ideally the surgeon, fellow or resident of thoracic surgery, who initially acts as a bedside assistant, progresses to being console surgeon. As several studies have shown the benefits of simulation (13,14), we state that working on the simulator to achieve proficiency should be compulsory before the trainee is allowed to move to the console.…”
Section: (I) Ascertain a Long-term Plan To Implement Robotic Thoracicmentioning
confidence: 99%
“…As a result, the learning curve for robotic laparoscopic surgery is much shorter [22][23][24][25]. While manual laparoscopy is still a required training, there have been studies in comparing the use of surgical robots by surgeons experience or inexperience with manual laparoscopy [26,66,67].…”
Section: Innovations For Accessibility: Sil and Notesmentioning
confidence: 99%